Determining the Knowledge Level and Accessibility of Major ICT Tools by Farmers in Madhya Pradesh - Kumar , Sarvesh (Indian Journal of Extension Education, 2025)
Information Communication Technologies are vibrant ways to significantly boost the agricultural sector by providing farmers with access to vital information, input availability, and online financial transactional services like DBT covering PM-KISAN Samman Nidhi, agri-input subsidies, and domestic gas subsidies. The study was conducted in 2024 to find out the major ICTs tools’ use, accessibility, knowledge level, and major barriers faced in use by collecting data from 150 randomly sampled farmers of Harda district of Madhya Pradesh. Data were collected by using a pre-tested structured interview schedule and analyzed with appropriate statistical tools. The majority of respondent farmers (68.45%) had a medium knowledge level about ICT tools. Education, annual income, social participation, mass media exposure, and extension contact expressed significant positive correlation with accessibility of major ICT tools among farmers. The major barriers were observed with Garrett’s ranking techniques. The farmers, especially young farmers, possessed the ICT tool like a smart mobile only for personal entertainment and interconnectivity, rarely using it to access agricultural knowledge for improvement. The backstopping of farmers to boost digital literacy for agricultural development and ICT adoption could be augmented by organizing educational campaigns and training.
Keywords: Accessibility; Agricultural knowledge; Awareness; Barriers; Financial benefits; ICTs